Institutionalization of pharmaceutical care in the municipality of Rio Maria, State of Pará, Brazil (Research, Society and Development, 2025)
Objective: to present information and data on the demographic, socioeconomic, epidemiological, governance and pharmaceutical services management characteristics of the municipality of Rio Maria, Pará. Methodology: This is an exploratory, descriptive and analytical study, retrospective for the years 2020 and 2023. Results: Rio Maria has an estimated population of 18,384 inhabitants. It has a GDP per capita of R$ 33,055.36. HDI-M of 0.638. Infant Mortality Rate of 11.36 deaths per thousand births in 2023. Regarding the institutionalization of pharmaceutical services, there are three pharmacists working in the municipality. There are no pharmacists working in the Basic Health Units and in the Central Pharmacy. Pharmaceutical Assistance is included in the Municipal Health Plan, the Annual Health Program, the Budget Guidelines Law, the Annual Budget Law, the Multi-Year Plan and in the reporting to the Municipal Health Council. The techniques of governance, management by results and strategic planning are not applied in the Pharmaceutical Assistance Coordination. Regarding technical-managerial and technical-assistance actions, it is clear that there is no notification of complaints or adverse events to medications to the Health Surveillance Notification System or to report the occurrence of adverse events related to medications or vaccines, among other points. Conclusion: There are problems to be overcome in the implementation and implementation of Pharmaceutical Assistance regarding the dimensions of human resources, governance, planning, management, structure, organization, sectoral policies, technical-managerial actions and technical-assistance actions.